Social and psychological determinants of socialization of adolescents - Ogorodnijchuk, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article describes the specifics of the process of socialization teenager in today's society and the teenage itself. We describe the basic social and psychological determinants that lead to the process of socialization. We uncovered the problems associated with the violation of socialization, which are manifested in the social and individual psychological level.
Keywords: society; socialization; family; deviant behavior; personality